Estado nutricional y hábitos alimentarios en donantes voluntarios del centro hemodador regional de Loreto tipo II, 2024 - Cumapa Cordova, Alpha Miranda (2025)
The present research studies the relationship between nutritional status and eating habits in volunteer donors from the Loreto regional hemodialysis center type II. We used a quantitative, descriptive, correlational and cross-sectional design made up of a sample of 250 volunteer donors. Data were collected through surveys, anthropometric measurements (BMI, abdominal perimeter and body fat) and food intake records. The results reveal that 45.2% of the donors had a healthy weight, while 34.4% were overweight and 13.6% moderately obese. In addition, a high percentage of body fat was observed, especially in men. Regarding eating habits, a high consumption of carbohydrates was identified (rice 89%, bread 65%, green banana 43%), along with a deficit in the intake of proteins and iron, mainly in women aged 20 to 39 years. A statistically significant relationship was identified with nutritional status and its indicators (BMI, abdominal circumference and body fat), but not with dietary habits. This suggests that other factors may influence the nutritional status of donors. It is determined that it is essential to strengthen the nutritional education system in the donor population in order to promote healthier eating habits and thus reduce the risk of chronic diseases. It is recommended to strengthen the infrastructure of the blood donation center, train staff in nutritional assessment and create nutritional education programs to promote health in donors.